Celebrity endorsed music videos: innovation to foster youth health promotion. - Macnab, A J; Mukisa, R (Health Promotion International, 2019)
There are calls for innovation in health promotion and for current issues to be presented in new and exciting ways; in addition to creating engaging messages, novel ways to deliver health messaging are needed, especially where youth are the key target audience. When pupils in WHO Health Promoting Schools were asked what health messages would resonate with them, they also identified celebrities as the 'messengers' they would be particularly likely to listen to. Expanding on these discussions, the pupils quoted celebrity-recorded music videos containing health and lifestyle messaging as an example of where they had learned from celebrities. Their ability to sing phrases from the songs and repeat key health messages they contained indicated the videos had commanded attention and provided knowledge and perspectives that had been retained. We located on YouTube the video titles the pupils identified and evaluated the content, messaging and production concepts these celebrity-recorded music videos incorporated. All are good examples of the health promotion genre known as education entertainment, where educational content is intentionally included in professionally produced entertainment media to impart knowledge, create favorable attitudes and impact future behaviors. The importance of this genre is growing in parallel with the burgeoning influence of social media. Music videos resonate with youth, and celebrity recordings combine young people's love of music with their fascination for the aura of celebrity. Hence, producing videos that combine an effective health message with celebrity endorsement offers potential as an innovative conduit for health promotion messaging among youth.